Analyzing the linguistic features of Patricia McCormick’s ‘Sold’: The significance of critical stylistics in literary discourse - Al-Zubaidi, Rasha Tareq Awad (Research Journal in Advanced Humanities, 2023)
This study pragmatically investigates incivility in the first Trump-Biden American political debate. This topic is chosen for its significant negative impact on both individuals and society as a whole, particularly in the political arena. The current study endeavors to achieve the following aims:(1) Specifying the types of incivility used in the Trump-Biden first American political debate, (2) Identifying the prevailing functions of incivility in the chosen data, (3) Finding out the pragmatic strategies employed by the two rivals. To achieve these aims, the following procedures are adopted: (1) Presenting a literature review about the pragmatics of incivility, (2) Adopting an eclectic model to analyze the chosen data pragmatically, and (3) Analyzing the data both qualitatively and quantitatively to come up with some conclusions. The fundamental conclusion of the current study is that debaters in American political debates employ three types of incivility, namely, invectives and ridicule, hyperbole and distortion, and emotionality and histrionics. These three types are pragmatically realized through different pragmatic strategies, such as speech acts, non-observance of maxims, impoliteness strategies, and argumentative appeals.